2014
DOI: 10.11648/j.jgo.20140204.14
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Delivery Service Utilization and Associated Factors among Child Bearing Age Women in Goba Woreda, Ethiopia

Abstract: Abstract:In despite of skilled delivery is one of the most tracked Millennium Development Goal indicators, the proportion of births attended by skilled health personnel in Ethiopia is very low. This study aimed at assessing level of institutional delivery service utilization and associated factors among mothers who gave birth during the last twelve months prior to this study. A community based cross sectional study design which is supplemented by qualitative method was conducted on April 2013 in Goba Woreda. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
40
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 12 publications
13
40
4
Order By: Relevance
“…This indicates that nearly half of mothers were delivered at home without the help of SBA to rescue the life in emergency situation. The current finding is consistent with the findings reported from SSA, Nepal, East Delhi India, and Ethiopia, where the proportion of mothers who gave birth in health facility were 53, 48, 51, 47 and 48.3% respectively [3, 11, 12, 20, 21]. However, the current prevalence of health facility delivery is higher when compared to reports from districts of Ethiopia, where the proportion of mothers who gave birth at health facility were 15.7, 37.9 and 25% respectively [17, 22, 23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that nearly half of mothers were delivered at home without the help of SBA to rescue the life in emergency situation. The current finding is consistent with the findings reported from SSA, Nepal, East Delhi India, and Ethiopia, where the proportion of mothers who gave birth in health facility were 53, 48, 51, 47 and 48.3% respectively [3, 11, 12, 20, 21]. However, the current prevalence of health facility delivery is higher when compared to reports from districts of Ethiopia, where the proportion of mothers who gave birth at health facility were 15.7, 37.9 and 25% respectively [17, 22, 23].…”
Section: Discussionsupporting
confidence: 92%
“…Literatures from Ethiopia also reported that institutional delivery ranges from 15 to 47% [11, 15]. So as to compensate this gap, Ethiopia in its health sector transformation plan has set a goal to increase SBA to 90% by 2019/20 [16].…”
Section: Introductionmentioning
confidence: 99%
“…But it is inconsistent with many others which reported current maternal age as the factor affecting place of delivery [4, 7, 8]. Contrary to many studies, the current study reported that women’s literacy status did not an have association with place of delivery [7–9, 11, 12]. Consistent with many other studies, the current study reported that decision maker [8, 9, 11], husbands’ education [11] and habit of listening radio [8, 9, 11] , did not significantly influence the choice of place of childbirth.…”
Section: Discussioncontrasting
confidence: 91%
“…Contrary to many studies, the current study reported that women’s literacy status did not an have association with place of delivery [7–9, 11, 12]. Consistent with many other studies, the current study reported that decision maker [8, 9, 11], husbands’ education [11] and habit of listening radio [8, 9, 11] , did not significantly influence the choice of place of childbirth. Even though pastoral mobility was claimed as one cause of the difficulty in providing health care to pastoralists, the current study did not show a significant association between extent of household mobility and the place of childbirth.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation